Marine nitrogen fixers mediate a low latitude pathway for atmospheric CO2 drawdown - Pearse J. Buchanan (Nature Portfolio, 2019)
Iron fertilisation of the high latitude oceans is a well-established biological mechanism to explain the ice age drawdown of atmospheric CO2, yet modelling has so far struggled to account for a sufficient drawdown via this mechanism. Here, the authors propose that N2 fixers, which inhabit the lower latitude ocean, made a significant contribution to CO2 drawdown and so amplified the global response to iron fertilisation during ice ages.